An ultra-small thermosensitive nanocomposite with a Mo154-core as a comprehensive platform for NIR-triggered photothermal-chemotherapy. Issue 2 (6th December 2017) - Zhang, Simin; Chen, Haobin; Zhang, Guohua; Kong, Xueping; Yin, Shengyan; Li, Bao; Wu, Lixin
Abstract : A novel route to use a giant POM cluster-based supramolecular complex as a new kind of photothermal-chemotherapeutic agent. Abstract : A uniform ultra-small (<10 nm) nanosized dendritic composite was reported for combined photothermal-chemotherapy, wherein a giant ring-like polymolybdate cluster was introduced for the first time as a photothermal therapeutic agent. The giant polyoxometalate cluster possesses strong absorption characteristics in the near infrared region, whereas it has never been applied for biomaterials due to its sensitivity towards environment and structural instability under physiological conditions. Herein, a cationic dendron bearing triethylene glycol monomethyl ether terminal groups was used to cover a giant polyanionic cluster Mo154 surface through a simple electrostatic interaction. Arising from their assembly, the formed core–shell supramolecular composite that has uniform size, precise chemical composition and definite molecular weight not only exhibited mono-dispersion and low cytotoxicity, but also imparted anticancer drug loading and thermoresponsive properties, thus leading to NIR-controlled drug release. When irradiated with an 808 nm NIR laser, the formed complex had significant in vivo photothermal-chemotherapeutic effects on tumor tissue, which makes it a promising material for applications in nanomedicine.